Investigation of Temperature Sensors Based on Si (P, Ni) - S.S. Nasriddinov (Журнал нано- та електронної фізики)
The paper presents the investigation results of the characteristics of a new type of temperature sensor based on silicon nanoclusters of nickel atoms in extreme conditions. It is shown that such sensors have high sensitivity and speed; they can successfully operate at elevated radiation and vibration.